Phthalate Exposure, PPARα Variants, and Neurocognitive Development of Children at Two Years - Yu, Ling; Zhang, Hongling; Zheng, Tongzhang; Liu, Juan; Fang, Xingjie; Cao, Shuting; Xia, Wei; Xu, Shunqing; Li, Yuanyuan (Frontiers in Genetics, 2022)
Background: The PPARα gene may be crucial to the neurotoxic effect of phthalates. However, epidemiological studies considering the neurodevelopmental influence of phthalates interacting with genetic susceptibility are limited. We hypothesized phthalates could interact with the PPARα gene, synergistically affecting neurocognitive development. Methods: A total of 961 mother-infant pairs were involved in this study. The concentrations of phthalate metabolites in maternal urine during pregnancy were detected. Children’s neurocognitive development was estimated with the Bailey Infant Development Inventory (BSID). Genetic variations in PPARα were genotyped with the Illumina Asian Screening Array. We applied generalized linear regression models to estimate genotypes and phthalate metabolites’ association with children’s neurocognitive development. Results: After adjusting for potential confounders, the mono-n-butyl phthalate (MnBP) concentration was negatively associated with PDI (β  =  −0.86, 95% CI: −1.67, −0.04). The associations between MnBP and neurocognitive development might be modified by PPARα rs1800246. Compared with low-MnBP individuals carrying rs1800246 GG genotypes, high-MnBP individuals with the AG + AA genotype had a higher risk of neurocognitive developmental delay, with the odds ratio of 2.76 (95% CI:1.14, 6.24). Conclusions: Our current study revealed that prenatal exposure to MnBP was negatively correlated with children’s neurocognitive development, and PPARα rs1800246 might modify the association. Keywords: phthalate metabolites, child neurodevelopment, PPARα, genetic variants, gene-environment interaction.